Managing Uncertainties in Human Resource Management during the COVID-19 Pandemic - Soraya, Evitha; Rugaiyah; Rosidi, Unifah; Sujanto, Bedjo (Future Science / FSH-PH Publications, 2023)
This study aimed at providing information to help HR practitioners understand the uncertainties caused by COVID-19 by addressing questions on what certainties are faced by HR practitioners in the education sector; what factors are seen as stressors, what characteristics need to be developed, and what solutions are proposed to overcome uncertainties in this pandemic of COVID-19. This qualitative study used a cross-sectional survey design. Electronic questionnaires were employed to collect qualitative data from 40 respondents based on purposive sampling. The study reveals that there are various types of uncertainties faced by HR managers or practitioners, ranging from organization operation to the ability to predict employees’ plans and actions. The main stressor during the pandemic is employees' safety perceptions of threats and risk of COVID-19 transmission. Others are the drastic change in the way of work and job insecurity and lack of valid information about COVID-19. Resilience, tolerance, and curiosity are the qualities that need to be developed by HR managers or practitioners. To overcome the uncertainties, HR Managers and practitioners could provide training on technology and competency development as the best strategy to overcome the uncertainties. Optimizing channels of communication, preparing transparency plans, providing facilities to support teleworking management, and arranging of work flexibility policy are alter strategies.